2011
DOI: 10.1002/hlca.201100116
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Poly‐Aib Oligopeptides and Aib‐Containing Peptides via the ‘Azirine/Oxazolone Method’, and Their Crystal Structures

Abstract: The protected poly‐Aib oligopeptides Z‐(Aib)n‐N(Me)Ph with n=2–6 were prepared according to the ‘azirine/oxazolone method’, i.e., by coupling amino or peptide acids with 2,2,N‐trimethyl‐N‐phenyl‐2H‐azirin‐3‐amine (1a) as an Aib synthon (Scheme 2). Following the same concept, the segments Z‐(Aib)3‐OH (9) and H‐L‐Pro‐(Aib)3‐N(Me)Ph (20) were synthesized, and their subsequent coupling with N,N′‐dicyclohexylcarbodiimide (DCC)/ZnCl2 led to the protected heptapeptide Z‐(Aib)3‐L‐Pro‐(Aib)3‐N(Me)Ph (21; Scheme 3). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…In the peptide 12d, the Phe(2Me) and the two consecutive Ac 5 c residues also show torsion angles (Table 3), which indicate two consecutive b-turns of type III' (III) [4] and the beginning of a 3 10 -helix structure stabilized by two consecutive intramolecular 4 3 1 H-bonds between N(7)ÀH´´´O (14) and N(4)ÀH´´´O (11). The N´´´O distances ( Table 4) are again in good agreement with the expected values [36].…”
Section: Starting Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the peptide 12d, the Phe(2Me) and the two consecutive Ac 5 c residues also show torsion angles (Table 3), which indicate two consecutive b-turns of type III' (III) [4] and the beginning of a 3 10 -helix structure stabilized by two consecutive intramolecular 4 3 1 H-bonds between N(7)ÀH´´´O (14) and N(4)ÀH´´´O (11). The N´´´O distances ( Table 4) are again in good agreement with the expected values [36].…”
Section: Starting Materialsmentioning
confidence: 99%
“…A useful method for the introduction of a,a-disubstituted a-amino acids into peptides is the so-called azirine/oxazolone method, in which 2,2-disubstituted 2H-azirin-3-amines (3-amino-2H-azirines) are used as amino-acid synthons [6]. This strategy has been widely employed in the synthesis of peptaibols [7 ± 9], endothiopeptides [10], and conformationally restricted cyclic peptides [11] [12]. A further application is the synthesis of cyclic depsipeptides containing a,a-disubstituted a-amino acids by employing a combination of the azirine/ oxazolone method and the so-called direct amide cyclization [13 ± 18].…”
mentioning
confidence: 99%
“…Introduction. -Since the elaboration of the 'azirine/oxazolone method' as a convenient protocol for the synthesis of Aib-containing peptides [1][2][3], this procedure has been used successfully for the preparation of model peptides [2c] [3][4][5][6], sterically congested oligopeptides [7] [8], and peptaibols [2d] [9][10][11]. It has also been shown that the method can be adopted to solid-phase methodology [12].…”
mentioning
confidence: 99%
“…Like other α,α-disubstituted α-amino acids, the presence of 5 forces peptides to form β-turns [12] or helical conformations. In our studies towards the synthesis of such sterically congested oligopeptides with a helical conformation by using the 'azirine/oxazolone method' [25][26][27][28][29], we introduced N-(2,2-dimethyl-2H-azirin-3-yl)proline methyl ester as a dipeptide (Aib-Pro) synthon [30][31][32] as well as other dipeptide (Xaa-Pro) synthons, including those with Xaa being a heterocyclic α-amino acid [13,33,34]. The aim of the present study was the synthesis of (S)-N-(1-aza-6-thiaspiro[2.5]oct-1-en-2-yl)proline methyl ester (1c) and its use as a…”
mentioning
confidence: 99%